Pembinaan Nilai-nilai Demokrasi Dalam Budaya Lokal Untuk Resolusi Konflik Pada Siswa Di SMA Negeri 17 Pulau Buano Seram Bagian Barat - LarosTuhuteru (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2021)
Research to date has not found an effective pattern of efforts for civics education in character building for young people and democratic values; in schools, families, community leaders, religious leaders, traditional leaders, youth leaders, and social organizations. This study aims to understand the attitudes and behaviors of young people in schools and the role of democratic values ​​as a solution to character development of young generation in SMAN 1 Pulau Buano. The research procedure used a qualitative approach, which is descriptive. Data collection techniques were in forms of (1) in-depth interviews, (2) direct observation, and (3) documentation studies. The sample was selected purposively and the research data were processed through a reduction process and descriptive qualitative analysis. After the results were analyzed, it was found a pattern of character building for the young generation in SMAN 1 Pulau Buano, effectively carried out with Civic Education approaches and democratic values ​​in schools, including: (1) value ​​of togetherness, (2) value of freedom, (3) value tolerance, (4) mutual cooperation (5) the value of consensus. It indicates that the harmony in school and community life will be achieved in accordance withthe absence of disputes among schools, young people, communities, ethnic groups, and religions. It can be concluded that developing the attitudes and character of the young generation and the values ​​of democracy in schools can develop brotherhood, cooperation, tolerance, harmony, responsibility, self-control, and mutual respect.